Ecological and biochemical peculiarities of maple genus in the urban environment (Case study: Norway and Ash-leaved maple) - Petr Anatolyevich Kuzmin; Ajgul Muhametnagimovna Kuzmina; Irina Leonidovna Bukharina; Konstantin Evgenievich Vedernikov; Raya Salikhovna Zaripova (Caspian Journal of Environmental Sciences, 2020)
The study demonstrates the results of ecological and biochemical studies of Norway maple and ash-leaved maple growing in a large industrial center. High activity of ascorbinate oxidase was recorded in June, and a low one in August. The content of ascorbic acid decreases during the growing season in anthropogenic plantations. Under an increased air content of pollutants, representatives of the maple genus show an increase in the activity of polyphenol oxidase in comparison with the control plantations. It should be said that the content of condensed tannins in the leaves decreases. In the roadside plantations of Norway maple, under the most intense load, in July, the peroxidase activity in the leaves is lower than in the conventional control plantations, and in August it is higher than in control.